OMNIBUS LAW SEBUAH PROBLEMATIK DAN PARADIGMA HUKUM DI INDONESIA - Zico Junius Fernando; Wiwit Pratiwi; Yagie Sagita Putra (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2021)
Abstract: This study uses a normative legal research method in the form of library research, which is conducted by collecting primary, secondary and or tertiary legal materials. The technique of collecting materials used in this research is literature study, which is carried out by identifying literature in the form of statutory regulations, books, official documents, papers, and several other sources related to this research. Then, the whole material that has been collected, the authors process and make an analysis of the collected material. The materials that have been collected are analyzed qualitatively and to classify legal materials, the authors use content analysis. This study discusses the concept of Omnibus Law whose ultimate goal is to find a solution to legal certainty in Indonesia. Whether the Omnibus Law approach can provide legal harmonization in Indonesia or vice versa, it raises new problems, but it is hoped that in the future the Law resulting from the Omnibus Law concept can lead to a Law that can cover all the rules as a whole so that the ideals of this concept can be realized well. Keywords: Omnibus Law, Problematics, Legal Paradigms